[PP.33.08] LONGITUDINAL LEFT VENTRICULAR CONTRACTILITY AND ISOLATED SYSTOLIC HYPERTENSION IN THE YOUNG. (September 2016) - Piskorz, D.; Tommasi, A.
Abstract : Objective: Background: Increased stroke volume and an unusual elevated amplification of the pulse wave are the main substratum of isolated systolic hypertension in the young. Objectives: to compare systolic and diastolic function in young isolated systolic and systolic-diastolic hypertensives to young normotensives. Design and method: Design and methods: under 40 years old non treated consecutives isolated systolic hypertensives, systolic-diastolic hypertensives and normotensives controls were included in a case control design. Left ventricular mass assessed by Devereux method, left ventricular hypertrophy considered > 95 g/m2 in women and > 115 g/m2 in men. Transmitral diastolic peak early flow to septal/lateral mitral annulus average peak early diastolic velocities (E/e' ratio) measured. Systolic function assessed by tissue Doppler average interventricular septum/lateral wall mitral annulus rate systolic excursion (s wave). Left ventricular end diastolic volume, end systolic volume, stroke volume, stroke work and systolic stress were measure by volumetric methods and corrected by body surface. Statistical analysis by ANOVA test, statistically significant p < 0, 05. Results: Results: 10 controls, 24 systolic – diastolic hypertensives and 14 isolated systolic hypertensives were included. Data are showed at the table. Figure. No caption available. Conclusions: Conclusions: 1) LV end diastolic volume is increased in isolated systolic hypertension in the young which by Franck Starling law could recruit myocardial fibers and increased longitudinal LV contractility; 2) exaggerated LV longitudinal shortening could explain the increased stroke volume in isolated systolic young hypertensives.